2020
DOI: 10.3389/fnut.2020.00148
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Meat and Australia's Generation Z

Abstract: This exploratory study of Gen Z consumers (n = 227) examines perceptions and opinions about cultured meat of young adults residing in Sydney, Australia. It uses an online survey and describes the findings quantitatively and through the words of the study participants. The results show that the majority (72%) of the participants are not ready to accept cultured meat; nonetheless, many think that it is a viable idea because of the need to transition to more sustainable food options and improve animal welfare. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
4
27
2
Order By: Relevance
“…In both the US and the UK, members of Gen Z were the most open to cultivated meat, whilst Baby Boomers were the least open. This is a notable contrast to recent research which was interpreted as suggesting that Generation Z may be particularly closed to cultivated meat [ 48 ]. In fact, this study did not compare different generations, and the low acceptance rates observed are more likely a result of methodology, particularly the stimuli presented to participants.…”
Section: Resultscontrasting
confidence: 86%
“…In both the US and the UK, members of Gen Z were the most open to cultivated meat, whilst Baby Boomers were the least open. This is a notable contrast to recent research which was interpreted as suggesting that Generation Z may be particularly closed to cultivated meat [ 48 ]. In fact, this study did not compare different generations, and the low acceptance rates observed are more likely a result of methodology, particularly the stimuli presented to participants.…”
Section: Resultscontrasting
confidence: 86%
“…The fact that older people reject "cell-based meat" to a greater extent confirms the results of another survey in Germany and France [49] and a recent European survey [46], both of which show that older respondents (65 years of age or older) have low acceptance of "cell-based meat". In contrast, in an Australian survey on the Generation Z, (18-24 years of age), considered to be familiar with technologies and with a sense of environmental responsibility, Bogueva and Marinova [30] reported that 72% of respondents from this younger generation are not ready to accept "cell-based meat" (compared to 3.1% of younger people between 18 to 30 years of age in our study who find this idea absurd and/or disgusting). The way in which the questions are worded or the difference in age or maturity of the respondents may explain this type of different observation.…”
Section: Hierarchical Classifications Of Quantitative and Qualitative Variables And Respondentscontrasting
confidence: 90%
“…A first approach to tackle this problem is to conduct online surveys to examine how consumers will react to "cell-based meat". Based on the consumers' perceptions and attitudes towards "cell-based meat", and their willingness to try, regularly eat, or buy it, these surveys have been conducted in different countries among various consumer groups, mainly focused on Europe [25][26][27][28] and the United States [29], but not exclusively [30][31][32][33][34][35], emphasizing that there were multiple factors influencing acceptance as well as rejection of "cell-based meat".…”
Section: Introductionmentioning
confidence: 99%
“…They further suggested other men who would normally eat meat but had experienced the vegan options. We were not interested in men who are usually vegetarian or vegan as they represent a very small fraction of Sydney's population, estimated at less than 6% [53]. We continued the recruiting of participants through snowballing until we achieved repetition of the issues raised during the interviews indicating data saturation or exhaustion of the number of unique opinions offered [54].…”
Section: Methodsmentioning
confidence: 99%
“…It allowed us to apply theoretical insights that are not exclusive to the analysed sample of young men and their particular circumstances but convey higher-level concepts [55]. This is described as analytical generalisation based on the transferability of the results on a case-by-case basis when similarities exist [53]. Therefore, it is essential to present thick description [56] of the cases that forms the basis for analysis and from which conclusions are drawn.…”
Section: Methodsmentioning
confidence: 99%